Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1523/eneuro.0099-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CaBP1/Caldendrin or CaBP2 Leads to Altered Ganglion Cell Responses

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…The procedures used in this study are not expected to produce pain or suffering in the animals. Generation of CaBP1 KO mice (RRID: MGI: 5780462) and CaBP2 KO mice was described previously (Kim et al, 2014;Sinha et al, 2016). Mice were maintained on a C57BL/6N (for CaBP1 KO) or C57BL/6J (for CaBP2 KO) background strains and housed in groups on a standard 12:12 hour light: dark cycle, with food and water provided ad libitum.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures used in this study are not expected to produce pain or suffering in the animals. Generation of CaBP1 KO mice (RRID: MGI: 5780462) and CaBP2 KO mice was described previously (Kim et al, 2014;Sinha et al, 2016). Mice were maintained on a C57BL/6N (for CaBP1 KO) or C57BL/6J (for CaBP2 KO) background strains and housed in groups on a standard 12:12 hour light: dark cycle, with food and water provided ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…We next analyzed ABRs and DPOAEs of CaBP2 KO mice. These mice were generated by replacing exons 1 and 2A with tdTomato and PGK neo cassette as well as stop codons in all 3 reading frames of exon 2B, which should prevent expression of all CaBP2 splice variants (Sinha et al, 2016). In contrast to the normal ABRs of 4 week-old CaBP1 KO mice ( Fig.…”
Section: Abrs Indicate Progressive Hearing Loss In Cabp2 Ko Micementioning
confidence: 99%
“…CaBPs are highly expressed in the retina where they may regulate the contribution of Ca v 1 channels to neurotransmitter release at ribbon synapses (Haeseleer et al, 2004; Haeseleer et al, 2000; Rieke et al, 2008; Sinha et al, 2016). CaBPs are also expressed in cochlear hair cells, where it was hypothesized that their antagonism of CaM may account for the very limited CDI of Ca v 1.3 channels (Cui et al, 2007; Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The success of retinal implant (a method of artificially replacing the function of retinal neurons, lost due to degenerative disease) depends on how effectively the prosthetic device maps the electrical stimulation pattern that can closely match the activity of RGC in terms of visual sensation. The recorded observations and temporal response of bipolar cells of RGCs revealed that the irradiance of the visual stimulus is proportional to the integrated voltage of PD of CIS [34] and the response of cells is non‐linear [35].…”
Section: Application Of the Proposed Mathematical Model As Activationmentioning
confidence: 99%